Low Serum Potassium Levels and Clinical Outcomes in Peritoneal Dialysis—International Results from PDOPPS - Simon J. Davies (2022)
Introduction: Hypokalemia, including normal range values <4 mEq/l, has been associated with increased peritonitis and mortality in patients with peritoneal dialysis. This study sought to describe international variation in hypokalemia, potential modifiable hypokalemia risk factors, and the covariate-adjusted relationship of hypokalemia with peritonitis and mortality. Methods: Baseline serum potassium was determined in 7421 patients from 7 countries in the Peritoneal Dialysis Outcomes and Practice Patterns Study (2014–2017). Association of baseline patient and treatment factors with subsequent serum potassium <4 mEq/l was evaluated by logistic regression, whereas baseline serum potassium levels (4-month average and fraction of 4 months having hypokalemia) on clinical outcomes was assessed by Cox regression. Results: Hypokalemia was more prevalent in Thailand and among black patients in the United States. Characteristics/treatments associated with potassium <4 mEq/l included protein-energy wasting indicators, lower urine volume, lower blood pressure, higher dialysis dose, greater diuretic use, and not being prescribed a renin-angiotensin system inhibitor. Persistent hypokalemia (all 4 months vs. 0 months over the 4-month exposure period) was associated with 80% higher subsequent peritonitis rates (at K <3.5 mEq/l) and 40% higher mortality (at K <4.0 mEq/l) after extensive case mix/potential confounding adjustments. Furthermore, adjusted peritonitis rates were higher if having mean serum K over 4 months <3.5 mEq/l versus 4.0–4.4 mEq/l (hazard ratio, 1.15 [95% confidence interval, 0.96–1.37]), largely because of Gram-positive/culture-negative infections. Conclusions: Persistent hypokalemia is associated with higher mortality and peritonitis even after extensive adjustment for patient factors. Further studies are needed to elucidate mechanisms of these poorer outcomes and modifiable risk factors for persistent hypokalemia.